2008
DOI: 10.1007/s12264-008-1017-2
|View full text |Cite
|
Sign up to set email alerts
|

An inhibition of ceruloplasmin expression induced by cerebral ischemia in the cortex and hippocampus of rats

Abstract: Objective To explore effects of cerebral ischemia on the ceruloplasmin (Cp) expression in the cortex and hippocampus of rats. Methods Male Wistar rats were randomly divided into cerebral ischemia group and control group. Cerebral ischemia was induced by ligating bilateral common carotid arteries and the ischemic rats were further subgrouped according to ischemia time. The control rats received a sham operation. The expression of Cp mRNA in the cortex and hippocampus was measured by reverse transcription polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Finally, some reports suggest that ATP7B might be involved in the synthesis of coagulation factors VIII and V [135,136]. Besides the liver, ATP7B expression has been detected in cells of neural origin and vascular endothelial cells [137,138]. It has been assumed that segments of the luminal loops of ATP7B participate in the direct transfer of copper to the active sites of intact Cp [139,140].…”
Section: Interplay Between Silver and Pathways Driving Intracellulmentioning
confidence: 99%
“…Finally, some reports suggest that ATP7B might be involved in the synthesis of coagulation factors VIII and V [135,136]. Besides the liver, ATP7B expression has been detected in cells of neural origin and vascular endothelial cells [137,138]. It has been assumed that segments of the luminal loops of ATP7B participate in the direct transfer of copper to the active sites of intact Cp [139,140].…”
Section: Interplay Between Silver and Pathways Driving Intracellulmentioning
confidence: 99%
“…2). Immunohistochemical studies of Cp in brain sections has previously identified expression in both cell types, 39 and it is unclear as to why cultured astrocytes do not display a Cu peak corresponding to Cp. A variety of Cu-60 binding proteins and peptides have been identified in astrocytes, including transporters (Copper transporter receptor 1 -Ctr1; divalent metal transporter 1 -DMT1; ATP7A), intracellular traffickers (SOD-1, copper chaperone for superoxide dismutase -CSS; ATOX1, Cox17), and storage and detoxifiers (metallothioneins -MTs).…”
Section: Diversity In Metalloproteins Between Cell Typesmentioning
confidence: 99%